An Exploration of Sustainability Reports via Systematic Literature Review: An Analysis of Progress in Promoting Sustainability - Prasetyawati, Tyas; Ferina, Ika Sasti; Yusnaini (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the development of sustainability reports and the factors that influence them. The research method employed is a Systematic Literature Review (SLR). This study presents 30 research articles obtained from the Scopus, Emerald, and Sinta databases, which were then classified according to specific criteria. The articles reviewed span from 2021 to early 2025. The development of research on sustainability reports has become an increasingly important topic. The findings indicate that research trends on sustainability reports have continued to grow each year. This suggests that both the public and the government are beginning to recognize the importance of environmental sustainability. The analysis reveals that several factors influence sustainability reports, such as leverage, firm size, and profitability. This study is expected to make an academic contribution by providing a comprehensive understanding of sustainability reports and offering directions for future research.